Global Economic Prospects and the Developing Countries 2000 (the international bank for reconstruction and development, 2000)
this report considers three areas where the crisis has had a major impact on growth and welfare in the developing world. First, the crisis has increased poverty in the East Asian crisis countries, Brazil, and the Russian Federation, and elsewhere. Chapter 2 reviews the evidence on the crisis' social impact on East Asia and other developing countries, and addresses the broader issue of the impact of external shocks on poverty in developing countries. Second, though the East Asian crisis countries are experiencing a strong cyclical recovery, severe structural problems remain. Chapter 3 outlines the depth of the problems faced by the corporate and financial sectors of these economies, analyzes the challenges facing the restructuring process, and discusses the appropriate role of government in supporting restructuring and reducing systemic risk. Third, exchange rate depreciations and declines in demand in East Asia exacerbated the fall in primary commodity prices that began in 1996. Chapter 4 examines how the most commodity-dependent economies in the world--the major oil exporting countries and the non-oil exporters of Sub-Saharan Africa--have adjusted to the commodity price cycle.